2013
DOI: 10.2119/molmed.2013.00036
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing Factor Receptor 2 Mediates Sex-Specific Cellular Stress Responses

Abstract: Although females suffer twice as much as males from stress-related disorders, sex-specific participating and pathogenic cellular stress mechanisms remain uncharacterized. Using corticotropin-releasing factor receptor 2-deficient (Crhr2−/−) and wild-type (WT) mice, we show that CRF receptor type 2 (CRF2) and its high-affinity ligand, urocortin 1 (Ucn1), are key mediators of the endoplasmic reticulum (ER) stress response in a murine model of acute pancreatic inflammation. Ucn1 was expressed de novo in acinar cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 59 publications
(86 reference statements)
2
36
1
Order By: Relevance
“…On the other hand, the concentric ER-derived structures, similar to SARC-like body, are detected in the acinar cells of pancreatitis induced by overstimulation of cerulein, a cholecystokinin analogue, in male mouse. 33 These findings support the view that the goat ceruminous glandular cells have highly secretory activity. Furthermore, the activation of IRE1α may participate in the homeostatic maintenance of these cells.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, the concentric ER-derived structures, similar to SARC-like body, are detected in the acinar cells of pancreatitis induced by overstimulation of cerulein, a cholecystokinin analogue, in male mouse. 33 These findings support the view that the goat ceruminous glandular cells have highly secretory activity. Furthermore, the activation of IRE1α may participate in the homeostatic maintenance of these cells.…”
Section: Discussionsupporting
confidence: 79%
“…Others and we have reported that Ucn1 actions are anti-inflammatory in the periphery [13,20], but the role of Ucn3 in mediating inflammation in the gut remains unknown. Rats with TNBS colitis failed to gain weight throughout the course of our study (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It is known that infusion of Ucn1 can ameliorate both colonic and pancreatic inflammation [13,20]. Whether Ucn3 is involved in the pathogenesis of GI disorders, such as Crohn’s colitis has not been studied before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of desensitization has received special attention considering that the failure of this signal regulation during recurrent exposure to stress may be causally related to pathological conditions ( 20 ) or the sex differences observed in the receptor rate of internalization could explain the increased vulnerability of females to stress-related disorders ( 136 ). Sex-dependent mechanisms have also been described in CRHR2 and UCN1-mediated stress-mediated inflammation responses ( 137 , 138 ).…”
Section: Crhrs Endocytosis: Desensitization and Signalingmentioning
confidence: 99%